DIVERSITY AND COMPOSITION OF VEGETATION IN JOMPI PROTECTED FOREST, SOUTHEAST SULAWESI, INDONESIA - Ernikawati Ernikawati; Dian Puspaningrum; Nurul Huda (Journal of Selvicoltura Asean, 2025)
Biodiversity in Indonesia is large and diverse. This biodiversity is the diversity of plants spread across various regions and forests. Forests themselves have several different types and functions, the most common of which is protected forests. One of the benefits of having protected forests is maintaining the environment and air quality. The reason for the need to conduct a forest habitat inventory. There are several potential areas, especially for plants, which can be utilized in the field of forest conservation.The purpose of this study was to examine the biological conditions and vegetation compilers include: density, frequency, dominance, and importance index in the Jompi Protected Forest, Muna Regency, Southeast Sulawesi. This study used the vegetation analysis method in a single plot measuring 100 x 100 m2, which was divided into 25 subplotst. The study was conducted from January to March 2024. Based on the findings, which encompassed 48 species and 28 families, the two species with the highest Importance Value Index were Tectona grandis (67,58%) and Gluta rengas (47,37%). In contrast to other types, a high Importance Value Index indicates that these species are better adapted to the individual environmental conditions. The level of diversity in the Jompi Protected Forest, based on these values ??is categorized as high with a diversity index (H>3.07) in the Protected Forest area. Furthermore, the abundance index can be categorized as moderately abundant in the seedling phase, E > 0.63) while the abundance index in the tree phase is classified as high with a value (E > 0.67).